Relationship between market and institutional networks and technological innovation: an analysis of peruvian manufacturing firms (2021)
Firms strive to develop technological innovations. This study focuses on two main objectives: to identify the relationship between market and institutional networks and technological innovation; and to analyze the relationship between the obstacles that f